Pengawasan Administrasi Kepegawaian Pada Bagian Umum Sekretariat Daerah Kota Palembang - Susilawati, Susilawati; Wulandari, Novita; Tahyudin, Didi (Mahesa Research Center, 2023)
This research aims to analyze and describe the supervision of Personnel Administration in the General Section of the Palembang City Regional Secretariat, as well as designing a model for supervision of personnel administration. This research used a qualitative method, with a total of 10 informants, using a purposive sampling technique. Data collection techniques used include: observation, interviews, documentation and literature study. The data analysis technique uses the Miles and Huberman interactive model. The results of this research show that the Supervision of Personnel Administration in the general section of the Palembang City Regional Secretariat is not yet optimal and needs improvement in various aspects, especially HR in the field of Personnel Administration which needs to understand the Main Duties and Functions of Administration. The form of supervision that can be applied to the General Section of the Regional Secretariat, especially regarding personnel administration, is the supervision of an administrative or administrative nature. Likewise, in the implementation of personnel administration which has the authority to appoint, transfer, and dismiss employees who have certain specifications, the supervision that can be carried out is administrative or administrative.